Zeolite Nanocomposites from Coal Fly Ash for Arsenic Removal in Wastewater - Erlinda Ningsih; Hanifah Sriamelia; Salsabilla (CV. Get Press Indonesia, 2026)
Arsenic contamination in wastewater poses serious environmental and public health risks because of its toxicity, persistence, and bioaccumulation potential. This study investigated the synthesis and performance of magnetic zeolite nanocomposites (MZN) derived from coal fly ash (CFA) for efficient As(V) removal from wastewater. CFA obtained from the PT PLN Ombilin Power Plant, West Sumatra, Indonesia, was converted into zeolite NaA/NaX through an alkaline hydrothermal method and subsequently modified with Fe₃O₄ nanoparticles to enhance adsorption capacity and magnetic separability. The synthesized MZN was characterized using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy with energy dispersive X-ray analysis (SEM-EDX), Brunauer–Emmett–Teller (BET), and vibrating sample magnetometer (VSM) analyses. Batch adsorption experiments were conducted to evaluate the effects of pH, contact time, adsorbent dosage, initial arsenic concentration, and temperature on adsorption performance. The maximum As(V) removal efficiency reached 97.4% under optimum conditions of pH 6, adsorbent dosage of 2 g/L, and contact time of 120 min. Adsorption behavior followed the Langmuir isotherm and pseudo-second-order kinetic models, indicating monolayer chemisorption. Thermodynamic analysis confirmed a spontaneous and endothermic process. Regeneration tests showed that MZN maintained over 85% removal efficiency after five adsorption–desorption cycles, demonstrating its potential as an effective, reusable, and low-cost adsorbent for industrial wastewater treatment.